2015
DOI: 10.1104/pp.15.01338
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Distribution and Interaction of the Arabidopsis SRSF1 Subfamily Splicing Factors

Abstract: Ser/Arg-rich (SR) proteins are essential nucleus-localized splicing factors. Our prior studies showed that Arabidopsis (Arabidopsis thaliana) RSZ22, a homolog of the human SRSF7 SR factor, exits the nucleus through two pathways, either dependent or independent on the XPO1 receptor. Here, we examined the expression profiles and shuttling dynamics of the Arabidopsis SRSF1 subfamily (SR30, SR34, SR34a, and SR34b) under control of their endogenous promoter in Arabidopsis and in transient expression assay. Due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…Furthermore, SR45 also co‐localized with OsFKBP20‐1b in cytoplasmic foci (Figure b). A recent study using leptomycin B and a fluorescence recovery after photobleaching assay showed that SR45 is a nucleocytoplasmic shuttling protein whose shuttling is mediated by the CRM1 pathway (Stankovic et al , ). Nevertheless, to date, the precise cytoplasmic localization of SR45 in plant cells has not been precisely determined because it is subject to rapid nucleocytoplasmic shuttling or is expressed at aberrant levels in transient assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SR45 also co‐localized with OsFKBP20‐1b in cytoplasmic foci (Figure b). A recent study using leptomycin B and a fluorescence recovery after photobleaching assay showed that SR45 is a nucleocytoplasmic shuttling protein whose shuttling is mediated by the CRM1 pathway (Stankovic et al , ). Nevertheless, to date, the precise cytoplasmic localization of SR45 in plant cells has not been precisely determined because it is subject to rapid nucleocytoplasmic shuttling or is expressed at aberrant levels in transient assays.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis encodes one SR45 gene ( AtSR45 ) that produces seven different mature transcripts via alternative splicing, while the rice genome harbours two SR45 gene copies because of duplication (Ali et al , ; Narsai et al , ). In addition to U1 snRNP 70K, several other SR proteins, including SC34‐like (SR33), RSZ1, SR30, SR34, and spliceosomal components SKIP and CACTIN, interact with SR45 to regulate pre‐mRNA splicing (Golovkin and Reddy, ; Mayeda et al , ; Golovkin and Reddy, ; Carvalho et al , ; Wang et al , ; Baldwin et al , ; Stankovic et al , ). Recent studies have indicated that SR45 plays an essential role in plant growth and adaptation to environment stress (Carvalho et al , ; Xing et al , ; Carvalho and Szakonyi, ; Albaqami et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Day et al (2012) have also reported an interaction between SR45 and the spliceosomal factor U2AF 35 , which in metazoans is involved in 39 splice site recognition (Wu et al, 1999;Wahl et al, 2009). Moreover, SR45 has been found to interact with three U5 small nuclear ribonucleoprotein proteins (Zhang et al, 2014) as well as with several other Arabidopsis SR proteins, namely, SCL33, RSZ21, SR30, SR34, and SR34a (Golovkin and Reddy, 1999;Zhang et al, 2014;Stankovic et al, 2016). Two other reported SR45-interacting proteins in Arabidopsis are the spliceosomal component SKIP (Wang et al, 2012), which confers salt stress tolerance (Feng et al, 2015), and CACTIN, an essential nuclear factor required for embryogenesis (Baldwin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies had shown that AFC2, a LAMMER-type protein kinase, is able to interact with and phosphorylate SR45 in vitro (Golovkin and Reddy, 1999) and found SR45 to be confined to the nucleus, either diffusely distributed in the nucleoplasm or concentrated in speckles, with its subnuclear dynamics being regulated by phosphorylation, ATP, and transcription (Ali et al, 2003;Ali and Reddy, 2006). However, recently reported evidence substantiates nucleocytoplasmic shuttling activity for SR45, with possible involvement of the nuclear exporter protein XPO1 (Stankovic et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, serine and arginine-rich protein 45 (SR45), a component of the spliceosome that interacts with three U5 small nuclear ribonucleo proteins (snRNPs) as well as with several other SR proteins (e.g. SCL33, RSZ21, SR30, SR34 and SR34a), is required for genome-wide pre-mRNA splicing in Arabidopsis (Golovkin & Reddy, 1999;Xing et al, 2015;Stankovic et al, 2016). However, SR45 is also a component of the apoptosis-and splicing-associated protein (ASAP) complex, which is involved in the silencing of FLC expression by Polycomb during vernalization in Arabidopsis (Q€ uesta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%